Masseter muscle hypertrophy: A case report. Issue 6 (November 2019) - Tsuneki, Masayuki; Maruyama, Satoshi; Yamazaki, Manabu; Niimi, Kanae; Kobayashi, Tadaharu; Nishiyama, Hideyoshi; Hayshi, Takafumi; Tanuma, Jun-ichi
Abstract: Masseter muscle hypertrophy is defined as the unilateral or bilateral expansion of the masseter muscle, and little is known about its etiology. Here we report a case of masseter muscle hypertrophy in a female patient in her 20 s who complained of facial asymmetry. Because of the hemifacial overgrowth of the right-side maxillofacial region from birth, she was thought to have congenital hemifacial hyperplasia. After orthodontic treatment and osteotomy, the patient underwent debulking of the right masseter muscle. Histologically, the surgical specimens exhibited thick masseter muscle fibers arranged irregularly. Masseter muscle cells exhibited diameters in the range of 20–60 μm.